2019
DOI: 10.28991/scimedj-2019-0103-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Optical Property of LaFeO3 Nanoparticles via Sol-Gel Combustion Method

Abstract: Perovskite LaFeO3 is one of the most useful materials for the application in a catalyst, gas sensors, and fuel cells, etc. LaFeO3 nanoparticles were synthesized by the citrate sol-gel method. According to the TG-DTA analysis on LaFeO3 xerogel powder, the proper crystallization temperature was found to be at 450 °C. The TEM images also show clear crystal formation was started at 450 °C. The LaFeO3 nanocrystalline particles were obtained by sintering the calcined powders at different temperatures (800 °C, 900 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Standardized precipitation index (SPI) is the most usable index in drought monitoring for its simplicity [21], and its accuracy compared to other indicators [31,32]. To follow the process, cumulative distribution function was first computed by gamma distribution function, fitted into time series.…”
Section: Methodology and Study Areamentioning
confidence: 99%
“…Standardized precipitation index (SPI) is the most usable index in drought monitoring for its simplicity [21], and its accuracy compared to other indicators [31,32]. To follow the process, cumulative distribution function was first computed by gamma distribution function, fitted into time series.…”
Section: Methodology and Study Areamentioning
confidence: 99%
“…This process is used in wastewater treatment as a result of their broad and high photocatalytic activities on the decomposition of various organic pollutants [137]. Nano-photocatalysts consist of nano-size order metal oxides, with semiconducting properties and strong ability to degrade large varieties of persistent organic pollutants such as dyes, detergents, pesticides, and volatile organic compound that WWTPs cannot remove [138,139]. Quite several semiconductors such as ZnO, SrTiO 3 , Fe 2 O 3, SnO 2 , CuO 2 , WO 3, and Fe 3 O 4 have been used for the decomposition of organic pollutants from different environmental matrices [139][140][141].…”
Section: Nanomaterials As Photocatalyst In the Degradation Of Ppcps Inmentioning
confidence: 99%
“…Nano-photocatalysts consist of nano-size order metal oxides, with semiconducting properties and strong ability to degrade large varieties of persistent organic pollutants such as dyes, detergents, pesticides, and volatile organic compound that WWTPs cannot remove [138,139]. Quite several semiconductors such as ZnO, SrTiO 3 , Fe 2 O 3, SnO 2 , CuO 2 , WO 3, and Fe 3 O 4 have been used for the decomposition of organic pollutants from different environmental matrices [139][140][141]. They can also be used for degrading halogenated and non-halogenated organic compounds, PPCPs, and heavy metals in some specific situations [7].…”
Section: Nanomaterials As Photocatalyst In the Degradation Of Ppcps Inmentioning
confidence: 99%
“…This refers to the Froude, Reynolds and Weber laws fulfillment at the same time. Theingi et al [35] concluded that employing very small scale models might influence the scour dimensions despite the limited advice given to modellers. The scour profile data must be normalized to provide for a comparison between varied experimental scales, and after a dimensional analysis of the governing quantities, it has been customary to non-dimensionalize the scour depth and the scour length by respectively employing the maximum scour depth, d sm , and the maximum scour length, L sm [36].…”
Section: Equipment and Testing Methodsmentioning
confidence: 99%